(untitled) (Diametros, 2009)
Hospital ethics committees were created in the United States of America in the 1970s. Their aims were the education of the hospital personnel in the field of ethics, the development of policies and the publication of guidelines concerning ethical issues, as well as consultations and case reviews of hospitalized patients when an ethical concern was present. During the last thirty years, these committees disseminated, particularly in Western Europe. In this manuscript, we describe the benefit, but also some difficulties with these committees, and we propose some solutions. The characteristics of these committees are discussed (i.e. typology of members, functioning and legitimacy). Finally, we carefully describe our local hospital clinical ethics committee in Geneva (Switzerland), which was founded in 1994 and it still very active. After fifteen years of experience, we remain strongly in favour of the implementation of such committees in any modern hospital.